MANIFESTASI KLINIS DAN DIAGNOSIS MIGREN VESTIBULAR - Freddy Sitorus,* Ni Nengah Rida Ariarini,* Dyah Tunjungsari* (Neurona Majalah Kedokteran Neuro Sains, 2018)
VESTIBULAR MIGRAINE VM IS THE MOST COMMON CAUSE OF RECURRENT SPONTANEOUS VERTIGO ON OUTPATIENT DIZZINESS CLINICS CLINICAL MANIFESTATION OF VM IS HIGHLY VARIABLE PATIENT MAY PRESENT SYMPTOMS LIKE VERTIGO DIZZINESS TINNITUS VISUAL DISTURBANCE PHONOPHOBIA PHOTOPHOBIA AURAL FULLNESS PARESTHESIA NAUSEA AND VOMITING